Foliose Lichen Diversity and Substrate Occurrence in Bukit Baranahu, Bukit Tangkiling Nature Park, Central Kalimantan, Indonesia - Risna Yanti Pasang Lolok; Vinsen Willi Wardhana; Frans Grovy Naibaho; Widya Krestina; Desimaria Panjaitan (Journal of Biotropical Research and Nature Technology, 2026)
Lichen diversity in Indonesia remains unevenly documented, with Kalimantan still underrepresented in current lichenological records. Bukit Baranahu, located within Bukit Tangkiling Nature Park, Central Kalimantan, is a lowland conservation area with socio-ecological importances, but information on its biodiversity, including foliose lichens, remains unavailable. This study aimed to identify foliose lichen taxa and describe their substrate occurrence in Bukit Baranahu. Field collection was conducted from May to October 2023 using an exploratory cruise survey combined with purposive sampling along accessible paths from the foothill toward the upper part of the hill. Specimens were examined based on morphological, anatomical, and chemical characters, including standard spot-test reactions. A total of 22 foliose lichen specimens were recorded and assigned to 17 taxa belonging to Caliciales and Lecanorales. Caliciaceae was the richest family, mainly represented by Dirinaria, whereas Parmeliaceae and Physciaceae were represented by fewer taxa. This composition differed from several Indonesian lichen inventories in which Parmeliaceae was commonly reported as a dominant family. Foliose lichens were recorded on living trees, snags or dead standing wood, fallen logs, and rocks, with living trees contributing the highest proportion of substrate records. Several taxa occurred on larger-diameter trees and snags, suggesting that substrate size, bark condition, and substrate stability may support local foliose lichen establishment. These findings provide the first baseline account of foliose lichen diversity and substrate occurrence in Bukit Baranahu and contribute to lichenological documentation in the underexplored lowland forests of Central Kalimantan.